Feasibility Test of Learning Media with Blended Learning Model and Augmented Reality-Assisted MOOCs - Risdianto, Eko; Wachidi, Wachidi; Riyanto, Riyanto; Fathurochman, Irwan; Yanto, Murni; Asmara, Adi (Jurnal Ilmiah Peuradeun, 2022)
This study aimed at testing the feasibility of Learning Media with Blended Learning Model and Augmented Reality-assisted MOOCs. The research was conducted at Bengkulu University in 2020. The research instrument consisted of a questionnaire to test the validity of the material, a questionnaire to test the validity of the blended learning model, and a questionnaire to test the validity of augmented reality-assisted MOOCs used in learning media. Each of the three questionnaires was filled out by 3 validators. The results of this study indicated that the 3 instruments used were valid. This was evidenced by the results of the validity calculation which states that all questions are valid and no questions are issued. The results of this study showed that the learning media developed was feasible to use both in terms of material, blended learning model design, and in terms of the augmented reality-assisted MOOCs used.